Collaboration and Integration Role in Mediating the Effect of Trust and Commitment on Supply Chain Performance - Fakhrian, M Bintang; Isfianadewi, Dessy (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2025)
The rise of the coffee shop business there is fierce competition in this industry. To remain competitive and succeed in the market, specific strategies are essential for achieving a competitive advantage. One common approach businesses use is to secure lower prices for raw materials to boost profits. To implement this strategy, supply chain management is necessary to help companies organize resource utilization and ensure that production is conducted in an efficient and balanced manner. The purpose of this study was to analyze the effect of trust and commitment on supply chain performance through collaboration and integration in coffee shops in Sleman Regency. The respondents involved in this study were 125 and analyzed using the SmartPLS3 application with non-probability convenience sampling techniques. The results of the analysis that has been carried out show that trust has a positive effect on collaboration, integration, and supply chain performance. Commitment has a positive effect on collaboration, integration, and supply chain performance. Collaboration has a positive effect on supply chain performance. Integration has no positive influence on supply chain performance. The results of this study can be taken into consideration for coffee shop businesspeople to realize the importance of trust, commitment, collaboration, and integration in supply chain performance.